THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN FOSTERING INNOVATION AND EMPLOYEE HAPPINESS IN THE WORKPLACE - Chen Rui; Wangshanyu; Hu Ying; Ooi Kok Loang; Jiang Mengyue; Tian Shuyan (International Journal of Accounting, Finance and Business, 2023)
This paper investigates the relationship between leadership styles and organisational performance and employee satisfaction. Effective leadership is essential for driving organisational success and nurturing a positive workplace culture. The study investigates the influence of various leadership styles, such as autocratic, democratic, laissez-faire, transformational, and transactional, on crucial organisational outcomes. The paper establishes a theoretical framework and a conceptual comprehension of leadership styles through a comprehensive review of the existing literature. It identifies the relationships between leadership styles and organisational performance indicators such as productivity, profitability, innovation, and employee satisfaction by analysing empirical studies. Combining qualitative interviews and quantitative surveys, the study collects data from a wide spectrum of organisations and industries using a mixed-methods approach. The acquired data is then evaluated using regression analysis and other statistical methods to put the hypotheses to the test. The results and discussion part investigates the impact of various leadership styles on organisational success and employee happiness, as well as the data analysis findings. It analyses and contrasts the findings with previous studies, noting any parallels or discrepancies and explaining the observed trends. The conclusion of the research project consists of a comprehensives assessment of the findings, with an emphasis on the study's theoretical, practical, and management implications. It acknowledges the limits of the research and makes suggestions for more research that should be conducted in the futures to deepen our understandings of different leadership styles and how they affect the performance of organisations and the happiness of their employees.